A STUDY ON SELECTION OF LOCATION BY RETAIL CHAIN: BIG MART - Karna , Mansi; Rai, Anusha; Karki, Bibek; Karna , Lavalesh; Rai, Miksen; Adhikari, Sangita (International Journal of Research -GRANTHAALAYAH, 2019)
Abstract This paper provides insight into the site-selection process that may have influenced the selection of location by retail chain store; Big Mart. The changing shopping habits and the birth of chain stores in and around Kathmandu and proceeds with the discussion on some of the models that have been used around the world. Selecting proper location for competitive advantages is a big choice for being the leader by co-creating customer and seller ecosystem. For this research, however, we have used the Analytical Hierarchy Process (AHP) and we will be delving more in detail with this method to understand the site selection method for our case area.